Linux High Availability : Red Hat EX436 and LPIC-3 304 : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2017)
Linux High Availability Complete Video Course: Red Hat EX436 and LPIC-3 304 has 8 hours of comprehensive video that teaches you everything you need to know about configuring and using High Availability in Linux. Uptime is a crucial part of your job. This title focuses on giving you the knowledge you need to maintain a high level of availability for you Linux servers. You will also find full hands-on labs, so you can get real-world experience while working your way through the course. The course can be used with all flavors of Linux, including Red Hat, Ubuntu, and SUSE. It also covers every objective in the Red Hat Certificate of Expertise in High Availability Clustering exam (EX436) and the High Availability portion of the Linux Professional Institute LPIC-3 304: Virtualization and High Availability exam.